2022
DOI: 10.1186/s13287-022-02897-x
|View full text |Cite
|
Sign up to set email alerts
|

A reduced level of the long non-coding RNA SNHG8 activates the NF-kappaB pathway by releasing functional HIF-1alpha in a hypoxic inflammatory microenvironment

Abstract: Background A series of biochemical responses, including hypoxia and aseptic inflammation, occur in periodontal ligament cells (PDLCs) during periodontal tissue remodeling of orthodontic tooth movement (OTM). However, the role of long non-coding RNA (lncRNA) in these responses is still largely unknown. We investigated the role of the lncRNA SNHG8 in hypoxic and inflammatory responses during OTM and explored the underlying mechanisms. Methods The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Sesamin increased osteogenesis by activating the Wnt/β-catenin pathway and decreased osteoclastogenesis via deactivating the NF-κB signaling pathway. Previous studies confirmed that deactivating the NF-κB signaling pathway inhibited osteoclast formation [ 53 ]. Further studies revealed that sesamin’s promoting effects on osteoblast were attributable to downregulation of DANCR expression.…”
Section: The Mechanism Of Snhgs Regulating Osteobl...mentioning
confidence: 64%
See 1 more Smart Citation
“…Sesamin increased osteogenesis by activating the Wnt/β-catenin pathway and decreased osteoclastogenesis via deactivating the NF-κB signaling pathway. Previous studies confirmed that deactivating the NF-κB signaling pathway inhibited osteoclast formation [ 53 ]. Further studies revealed that sesamin’s promoting effects on osteoblast were attributable to downregulation of DANCR expression.…”
Section: The Mechanism Of Snhgs Regulating Osteobl...mentioning
confidence: 64%
“…For example, we found that SNHG5 mediated periodontal inflammation via the NF-κB signaling pathway [ 41 ]. Another SNHG family member, SNHG8 , also affected the NF-κB signaling pathway and inflammatory processes [ 53 ]. We observed that in a hypoxic inflammatory microenvironment, decreased SNHG8 expression activated the downstream NF-κB signaling pathway.…”
Section: Prospectmentioning
confidence: 99%
“…The role of SNHG8 in brain function and disease is not well investigated. Recently, SNHG8 was reported to be involved in inflammation and microglial response by sponging miR-425-5p and SIRT1/NF-κB signaling (Tian et al 2021) and in orthodontic tooth movement (OTM)(C. Wang et al 2022). SNHG8 has been associated with an inflammatory response: reducing SNHG8, which binds to HIF-1α, leads to free functional HIF-1α and activation of the downstream NF-κB pathway (C. Wang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SNHG8 was reported to be involved in inflammation and microglial response by sponging miR-425-5p and SIRT1/NF-κB signaling (Tian et al 2021) and in orthodontic tooth movement (OTM)(C. Wang et al 2022). SNHG8 has been associated with an inflammatory response: reducing SNHG8, which binds to HIF-1α, leads to free functional HIF-1α and activation of the downstream NF-κB pathway (C. Wang et al 2022). The consideration of therapeutic strategies involving SNHG8 replacement will require an evaluation of the landscape of SNHG8 effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation